An Exhaustive Examination of the Integration of Literature into Teaching/Learning Strategies for Advancing English Reading Comprehension: A Systematic Literature Review - Abdulrazzaq, Dulfqar Mhaibes; Edan, Mahmoud Arif; Heidarzadegan, Nazila (ELE Reviews: English Language Education Reviews, 2024)
This study aims to provide an extensive literature review of previous studies conducted to demonstrate and investigate the effectiveness of using literature in teaching and learning reading comprehension at the middle education level. Consequently, this literature review was conducted using a systematic approach, involving searches across multiple academic databases on the addressed topic, which resulted in highlighting twenty articles conducted between 2010 and 2021. The systematic review method included identifying relevant studies, evaluating their quality, and synthesizing their findings. Furthermore, the researchers divided the main findings into two groups: the first one focused on using short stories, and the second group included all other literary genres. Both groups showed the positive effect of using short stories, comic stories, or novels as an efficacious method in developing, teaching, and learning reading comprehension skills, especially for adolescents and children. Therefore, this study suggests using different literary genres such as children’s short stories, fiction, and plays in middle education classrooms and employing new reading techniques and strategies to further motivate students. In addition, it recommends using a larger population and random assignment when selecting samples for future studies.